Особливості моделей утилізації різновидів полімерних відходів - Бухкало, Світлана Іванівна (НТУ "ХПІ", 2016)
В статті наведені можливості вирішення задач підвищення ефективності використання відходів різних галузей промисловості на комплексному підприємстві, яке може забезпечувати усі свої енергетичні потреби самостійно. Дослідження спрямовані на вивчення таких питань як організація збирання і транспортування відходів, їх класифікація-ідентифікація та методи контролю якості, маркування відповідно до загальноприйнятої класифікації полімерів; вибір науково-обгрунтованих методів переробки та утилізації полімерів; розробка необхідних технологічних схем, вибір добавок для модифікації та обладнання для переробки полімерних відходів; вибір підприємств для реалізації утилізації полімерів і виду енергетичних ресурсів для реалізації цих проектних рішень.

The materials are presented the possibilities of solving problems of improving the use of wastes of different industries on a complex enterprise that can provide all its energy needs alone. The problem of wastes utilization and recycling is present as complex research and analysis of energy- and resource saving processes for treatment of polymer wastes of various origin. The investigation are focused in researching such problems as organization of waste collection, transportation and sorting-identification of wastes according to adapted polymers classification; selection of scientific based methods of wastes to be utilized or recycled; the development of appropriated process flow sheets and choice of modifications additives and equipment for polymers waste recycling. The choice of appropriate plants with selected energy resources is very important for projects realization.
Properties models species recycling plastic waste
Keywords: комплексні енерготехнології; екологічна безпека; науково-обґрунтовані методи; переробка; утилізація; integrated energy technologies; packaging; evidence-based methods; ecological safety; wastes conversion